2000
DOI: 10.1161/01.cir.102.11.1270
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Habitual Exercise, and Dynamic Arterial Compliance

Abstract: Regular aerobic-endurance exercise attenuates age-related reductions in central arterial compliance and restores levels in previously sedentary healthy middle-aged and older men. This may be one mechanism by which habitual exercise lowers the risk of cardiovascular disease in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

76
881
12
36

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 944 publications
(1,005 citation statements)
references
References 41 publications
(30 reference statements)
76
881
12
36
Order By: Relevance
“…Since biochemical changes in the actual composition of the arterial wall are believed to occur over a period of years, 16 the changes in arterial compliance observed following close to 4 months of training in this study likely occurred through other means. One possibility is that increased pulse pressure and mechanical distension during exercise sessions stretched collagen fibers and modified their cross-linking, resulting in increased arterial compliance.…”
Section: Effects Of Fes-lce Training On Arterial Compliance D Zbogarmentioning
confidence: 78%
See 1 more Smart Citation
“…Since biochemical changes in the actual composition of the arterial wall are believed to occur over a period of years, 16 the changes in arterial compliance observed following close to 4 months of training in this study likely occurred through other means. One possibility is that increased pulse pressure and mechanical distension during exercise sessions stretched collagen fibers and modified their cross-linking, resulting in increased arterial compliance.…”
Section: Effects Of Fes-lce Training On Arterial Compliance D Zbogarmentioning
confidence: 78%
“…One possibility is that increased pulse pressure and mechanical distension during exercise sessions stretched collagen fibers and modified their cross-linking, resulting in increased arterial compliance. 16 Arterial compliance can also be altered via modulation of sympathetic-adrenergic tone of smooth muscle cells in the arterial wall that has been shown to be preserved below the lesion level in individuals with SCI. 17 It is possible that FES-LCE exercise improved arterial compliance by reducing the chronic suppressive influence of the sympathetic-adrenergic tone either directly or by improving the sympathoinhibitory effect of nitric oxide (NO), an important marker of endothelial health.…”
Section: Effects Of Fes-lce Training On Arterial Compliance D Zbogarmentioning
confidence: 99%
“…10 Previous studies have indicated that age-related increases in arterial stiffness were attenuated in higher-fit adults. 11,12 Moreover, arterial stiffness and BP were negatively associated with cardiorespiratory fitness. 13 When considering the pathophysiological implications of vascular stiffening, it is also important not to overlook changes in the heart to which the blood vessels are coupled.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it has been previously shown that the greatest improvements in cardiovascular health outcomes were observed among individuals with the most compromised fitness levels, including a reduced risk for cardiovascular-related mortality 41 and cardiovascular disease 42 and lowered arterial stiffness. 43 While physical inactivity is a known risk factor for atherosclerosis, only a few crosssectional studies have reported the inverse relationship between arterial stiffness and measures of physical activity or physical fitness, [44][45][46] and none focused on individuals with stroke. Augmented physical activity has the potential to improve arterial stiffness, even in the presence of aging.…”
Section: Discussionmentioning
confidence: 99%
“…Augmented physical activity has the potential to improve arterial stiffness, even in the presence of aging. Tanaka et al 43 found that sedentary and recreationally active men had lower central arterial compliance compared to endurance-trained men regardless of age group, suggesting that age-associated increases in arterial stiffness may be mitigated with regular aerobic exercise. Exercise training has also been shown to improve arterial stiffness among individuals with coronary artery disease, 47 older adults with multiple risk factors, 48 and those undergoing hemodialysis.…”
Section: Discussionmentioning
confidence: 99%